Adaptation of the Rose-Bengal test for the diagnosis of brucellosis - ΓΙΑΝΤΖΗΣ Δ. Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
2848 samples of bovine serum and 592 samples of sheep serum were examined simultaneously by the Rose - Bengal Test (R.B.T.), the serum Agglutination Test (S.A.T) and Complement Fixation Test (C.F.T.). It was observed that the results of the Rose-Bengal Test were parallel to those of the Complement Fixation Test (C.F.T.). The percentages of false negative reactions for the Rose-Bengal Test with the bovine and sheep sera were 2,4% and 3,2% respectively, while the percentages of false positive reactions were 1% and 4,7% respectively (compared with the reactions of the Complement Fixation Test).